2018
DOI: 10.1017/s0954579418001335
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parents and schools on developmental trajectories of antisocial behaviors in Caucasian and African American youths

Abstract: African American youths are overrepresented in the American juvenile justice system relative to Caucasians. Yet, research on antisocial behaviors (ASB) has focused on predominantly Caucasian populations. Furthermore, relatively little is known about how environmental factors, such as supportive parenting (e.g., how close adolescents feel to their parent) and school connectedness (e.g., how supported adolescents feel at school), affect trajectories of ASB in Caucasians versus African Americans. This study mappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…Regarding the relationships between parental response and adolescents' externalizing problems, this study indicated that a supportive response was most associated with reduced problem behaviors, whereas a self-focused response was associated with increased problem behaviors. While the first association is consistent with established findings in the literature (e.g., Morrison et al, 2019;Weitkamp & Seiffge-Krenke, 2019), only limited research to date has reported on the impact of a self-focused parental response on adolescents' externalizing problems. This type of self-involved response (i.e., the parents emphasize their own distress instead of addressing their child's distress) may translate into either or both (a) a lack of parental monitoring, or (b) some degree of parental stress, both of which represent risks for the adolescent's problem behavior (Hinnant et al, 2015).…”
Section: Situating Identity Distress In the Parenting-delinquency Relationshipsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the relationships between parental response and adolescents' externalizing problems, this study indicated that a supportive response was most associated with reduced problem behaviors, whereas a self-focused response was associated with increased problem behaviors. While the first association is consistent with established findings in the literature (e.g., Morrison et al, 2019;Weitkamp & Seiffge-Krenke, 2019), only limited research to date has reported on the impact of a self-focused parental response on adolescents' externalizing problems. This type of self-involved response (i.e., the parents emphasize their own distress instead of addressing their child's distress) may translate into either or both (a) a lack of parental monitoring, or (b) some degree of parental stress, both of which represent risks for the adolescent's problem behavior (Hinnant et al, 2015).…”
Section: Situating Identity Distress In the Parenting-delinquency Relationshipsupporting
confidence: 86%
“…Generally, it is established that parental monitoring is most associated with reduced problem behaviors (Hinnant et al, 2015; Hoeve et al, 2009), whereas dimensions of parental support and warmth are more closely related to reduced internalized distress (e.g., Fletcher et al, 2004). Nonetheless, parental support and warmth have also been associated with reduced externalizing behaviors (Morrison et al, 2019; Weitkamp & Seiffge-Krenke, 2019). For example, in a sample of 753 adolescents from high-risk communities, Bendezú et al (2018) found specific features of conversation with adolescents regarding daily activities to be the strongest, negative predictor of their delinquency.…”
Section: The Role Of Parenting Practicesmentioning
confidence: 99%
“…Third, hierarchical characterizations of psychopathology can potentially unravel more meaningful and precise risk and protective factors in a given population (Eaton et al, 2013;Morrison, Martinez, Hilton, & Li, 2018). That is, instead of focusing on discrete, categorical diagnoses that vary in prevalence across populations, latent factor scores can be examined instead, reflecting each person's risk on a broader dimension of psychopathology that is statistically comparable across racial-ethnic groups (de Jonge et al, 2018;Eaton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Third, HiTOP can potentially be applied to unravel more meaningful and precise risk and protective factors in a given population (Eaton et al, 2013;Morrison, Martinez, Hilton, & Li, 2018). Clinically, interventions can potentially be aided or improved by the knowledge that instead of creating treatments for discrete, categorical disorders that vary in prevalence across populations (which may be driven by socio-cultural factors), transdiagnostic latent factors can be focused on instead, given that latent factors reflect each person's risk on a broader dimension of psychopathology that is statistically comparable across racial-ethnic groups (Eaton et al, 2013;de Jonge et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there is a widely acknowledged overrepresentation of traumatized youth (Abram et al., 2004) among youth who are currently involved in the Juvenile Justice System, JJS (e.g., on probation, in diversion programs, in detention). Also importantly, youth of color and of low SES are overrepresented in the JJS (Morrison, Martinez, Hilton, & Li, 2019), and are underrepresented among youth identified as gifted and/or talented (Worrell, Subotnik, Olszewski‐Kubilius, & Dixson, 2019).…”
Section: Twice Exceptional and Delinquencymentioning
confidence: 99%